Ultrasounds in cancer therapy: A summary of their use and unexplored potential - Jesús Frutos Díaz-Alejo; Iciar Gonzalez Gomez; Julie Earl (Frontiers Media S.A., 2022)
Ultrasounds (US) are a non-ionizing mechanical wave, with less adverse effects than conventional pharmacological or surgical treatments. Different biological effects are induced in tissues and cells by ultrasound actuation depending on acoustic parameters, such as the wave intensity, frequency and treatment dose. This non-ionizing radiation has considerable applications in biomedicine including surgery, medical imaging, physical therapy and cancer therapy. Depending on the wave intensity, US are applied as High Intensity Ultrasounds (HIUS) and Low Intensity Pulsed Ultrasounds (LIPUS), with different effects on cells and tissues. HIUS produce thermal and mechanical effects, resulting in a large localized temperature increase, leading to tissue ablation and even tumor necrosis. This can be achieved by focusing low intensity waves emitted from different electrically shifted transducers, known as HIFU (High Intensity Focused Ultrasounds). LIPUS have been used extensively as a therapeutic, surgical and diagnostic tool, with diverse biological effects observed in tissues and cultured cells. US represent a non-invasive treatment strategy that can be applied to selected areas of the body, with limited adverse effects. In fact, tumor ablation using HIFU has been used as a curative treatment in patients with an early stage pancreatic tumor and is an effective palliative treatment in patients with advanced stage disease. However, the biological effects, dose standardization, benefit-risk ratio and safety are not fully understood. Thus, it is an emerging field that requires further research in order to reach its full potential.